A rare thoracic intraspinal schwannoma in twin pregnancy with aggravated clinical presence: A case report following CARE. Issue 11 (March 2017) - Chen, Ruiqi; Xiao, Anqi; Xing, Lu; You, Chao; Liu, Jiagang
Abstract: Introduction: This is the first case report about a thoracic intraspinal schwannoma in twin pregnancy with aggressive clinical presentation. Clinical presence and diagnoses: A 21-year-old woman presented with a 2-month history of back pain and slight lower extremity numbness and weakness, and her symptoms were misdiagnosed as normal reactions to pregnancy until she progressed to complete paralysis and incontinence within 2 weeks. She was then confirmed to have thoracic intraspinal schwannoma through MRI. Interventions and outcomes: Surgery was performed using a unilateral hemilaminectomy approach with a comfortable lateral position during operation. The patient exhibited significant improvements in sensation and muscle strength after surgery. She delivered 2 healthy baby girls by eutocia in her 38th week of pregnancy. Lessons: The diagnosis of this disease and the 4 possible mechanisms of its aggravated clinical presence are discussed. Intraspinal schwannomas during pregnancy are rare but may cause critical consequences for both the mother and the fetus. Timely diagnosis and multidisciplinary treatment by obstetricians, anesthesiologists, surgeons, oncologists, and neonatologists are essential for the clinical management of this disease.